(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Professional Learning Communities (PLCs) concept was introduced in the pre-tertiary education system in Ghana in 2019 as a model of continuous professional development policy, following the education reforms. The aim is to offer teachers opportunity to take charge of their own professional learning so as to become competent professionals in the field of education as well as to promote collaboration and collegiality among them. This study explored the challenges facing the basic school headteachers in Effutu Municipality of Ghana in the implementation of PLCs concept as well as the support systems they needed. It was qualitative research underpinned by the interpretivist paradigm and employed a case study research design. Using maximal variation sampling strategy, 15 headteachers were selected for a semi-structured interview and the data collected was analysed thematically. The study revealed that the challenges confronting the headteachers in the implementation of PLCs in the municipality included time constraints and limited space for reflective activities, perceived lack of value, and inadequate knowledge about the concept. It also emerged that financial and material support from both internal and external sources within the fraternity were needed for effective implementation of the PLCs in the municipality, The study recommended that the Municipal Education Directorate should intensify school sensitization campaigns to raise awareness, and to promote the benefits of PLCs among the headteachers, teachers, and relevant stakeholders to ensure effective implementation of the concept.